Low dielectric constant material with high heat resistance and high performance and preparation method thereof
By using a combination of polyphenylene sulfide, low-dielectric glass fiber, glass microbeads and metal salts, low-dielectric constant materials with high heat resistance and high performance are prepared, which solves the efficiency problem of traditional materials in electrical signal transmission, and achieves low dielectricization and high mechanical strength of the materials.
Patent Information
- Application Number
- CN202411863123.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional polymer materials have problems such as RC delay, signal loss and power loss in electrical signal transmission, which limits the improvement of communication efficiency.
Polyphenylene sulfide is used as the main matrix, combined with low dielectric glass fiber, glass microbeads and metal salts, and low dielectric constant materials with high heat resistance and high performance are prepared through twin screw extrusion molding.
It realizes low dielectricization and high mechanical strength of the material, while reducing the dielectric constant, improving the heat resistance and performance of the material. It has a simple process and no toxic gas production, making it suitable for large-scale production.
Smart Images

Figure BDA0005193664530000061 
Figure BDA0005193664530000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a low dielectric constant material with high heat resistance and high performance and a preparation method thereof. Background Art
[0002] As communication needs continue to rise, especially in the application scenarios of 5G technology, the importance of materials in electrical signal transmission has become increasingly prominent. However, traditional polymer materials often face problems such as RC delay, signal loss and power loss, which seriously restrict the improvement of communication efficiency. Therefore, innovative low-dielectric polymer materials have emerged and become a hot topic in current research.
[0003] The high heat-resistant low dielectric materials currently used in business are mainly based on polyimide, epoxy resin, and cyanate resin (CE), which are difficult to process and may produce toxic gases. The patent application with publication number CN 105694425 A discloses a polyphenylene ether resin composition, which contains: a modified polyphenylene ether copolymer, a polymer substance having a weight average molecular weight greater than the weight average molecular weight of the modified polyphenylene ether copolymer, and a compound compatible with the modified polyphenylene ether copolymer. The resin composition of the invention utilizes the properties of dielectric properties, high temperature resistance, and high glass transition temperature of polyphenylene ether and polybutadiene skeleton materials. However, traditional polyphenylene ether is incompatible with other resins (such as polybutadiene), so the (meth) acrylate skeleton is also introduced into the polybutadiene skeleton in the invention scheme, and a compound having more than 2 carbon-carbon unsaturated double bonds in one molecule and a melting point below 30°C and compatible with the modified polyphenylene ether copolymer is added to the composition.
[0004] However, compared with pure polyphenylene ether or 1,2-polybutadiene materials, the addition of (meth)acrylate skeletons or other compounds is not conducive to fully utilizing the various properties of the skeletons of polyphenylene ether and polybutadiene, so that the composition cannot fully utilize the dielectric properties, thermal properties and glass transition temperature of polyphenylene ether and polybutadiene materials. Summary of the invention
[0005] The object of the present invention is to provide a low dielectric constant material with high heat resistance and high performance and a preparation method thereof, so as to reduce the dielectric constant of the material.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A low dielectric constant material with high heat resistance and high performance comprises, by weight, 30-84 parts of polyphenylene sulfide, 5-50 parts of low dielectric glass fiber, 5-40 parts of glass microbeads, 0.5-5 parts of metal salt, 0.1-1 parts of antioxidant and 0.1-1 parts of silane coupling agent.
[0008] Furthermore, the polyphenylene sulfide (PPS) is one or a combination of PPS 3450, PPS GAC20, GAC09, GAC05, GAC03, PPS3490, PPS 3418 and PPS GAT05.
[0009] Furthermore, the glass microspheres are hollow glass microspheres.
[0010] Furthermore, the metal salt includes but is not limited to copper bromide, copper chloride and aluminum oxide.
[0011] Furthermore, the antioxidant is antioxidant S9228.
[0012] Furthermore, the silane coupling agent is one or a combination of epoxy silane coupling agent, amino silane coupling agent, and urea silane coupling agent.
[0013] A method for preparing a low dielectric constant material with high heat resistance and high performance, comprising the following steps:
[0014] Polyphenylene sulfide, low dielectric glass fiber, glass beads, metal salt, antioxidant and silane coupling agent are uniformly mixed to obtain a mixture; the mixture is put into a twin-screw basic machine and extruded to prepare a low dielectric constant material with high heat resistance and high performance.
[0015] Furthermore, during the extrusion molding process, the temperature of the twin-screw extruder is 280-320° C., and the rotation speed is 120-450 r / min.
[0016] Beneficial effects of the present invention:
[0017] (1) The present invention provides a low dielectric constant material with high heat resistance and high performance. By selecting polyphenylene sulfide as the main matrix, the material has high heat resistance; glass beads, low dielectric glass fibers and metal salts are used as the main fillers, and the glass beads and low dielectric glass fibers are used to achieve low dielectric constant of the material. At the same time, the presence of glass fibers makes it have excellent performance.
[0018] (2) The metal salt used in the present invention will form a metal complex with the sulfide bond in the polyphenylene sulfide, thereby improving the mechanical strength of the material, and the metal (copper) will further reduce the dielectric constant, thereby further enhancing the material performance.
[0019] (3) The preparation method provided by the present invention uses low-cost raw materials, is simple in preparation, easy to process, and does not produce toxic gases, and is suitable for large-scale production. DETAILED DESCRIPTION
[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Raw material models and suppliers: polyphenylene sulfide (PPS 3450, PPS 3418, PPS GAC20, PPS GAT05, PPSGAC05); copper bromide (Shanghai Aladdin Biochemical Technology Co., Ltd.); copper chloride (Shanghai Aladdin Biochemical Technology Co., Ltd.); alumina (Shanghai Aladdin Biochemical Technology Co., Ltd.); hollow glass microspheres (3M Company); low dielectric glass fiber (Taishan Glass Fiber); silane coupling agent (KBE903 Shin-Etsu); antioxidant (S9228).
[0022] Example 1
[0023] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 30 parts of polyphenylene sulfide (PPS 3450), 25 parts of glass fiber, 40 parts of hollow glass microspheres, 4 parts of copper bromide, 0.5 parts of silane coupling agent, and 0.5 parts of antioxidant S9228 were uniformly added into a 280°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0024] Example 2
[0025] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 84 parts of polyphenylene sulfide (PPS 3450), 5 parts of glass fiber, 5 parts of hollow glass microspheres, 5 parts of copper bromide, 0.9 parts of silane coupling agent, and 0.1 parts of antioxidant S9228 were uniformly added into a 320°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0026] Example 3
[0027] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 40 parts of polyphenylene sulfide (PPS 3450), 50 parts of glass fiber, 5 parts of hollow glass microspheres, 4 parts of copper bromide, 0.1 parts of silane coupling agent, and 0.9 parts of antioxidant S9228 were uniformly added into a 300°C, 450r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0028] Example 4
[0029] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 30 parts of polyphenylene sulfide (PPS GAC05), 25 parts of glass fiber, 40 parts of hollow glass microspheres, 4 parts of cupric chloride, 0.5 parts of silane coupling agent, and 0.5 parts of antioxidant S9228 were uniformly added into a 280°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0030] Example 5
[0031] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 30 parts of polyphenylene sulfide (PPS GAT05), 25 parts of glass fiber, 40 parts of hollow glass microspheres, 4 parts of alumina, 0.5 parts of silane coupling agent, and 0.5 parts of antioxidant S9228 were uniformly added into a 280°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0032] Example 6
[0033] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 30 parts of polyphenylene sulfide (PPS GAC20), 25 parts of glass fiber, 40 parts of hollow glass microspheres, 4 parts of copper bromide, 0.5 parts of silane coupling agent, and 0.5 parts of antioxidant S9228 were uniformly added into a 280°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0034] Example 7
[0035] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 30 parts of polyphenylene sulfide (PPS 3418), 25 parts of glass fiber, 40 parts of hollow glass microspheres, 4 parts of copper bromide, 0.5 parts of silane coupling agent, and 0.5 parts of antioxidant S9228 were uniformly added into a 280°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0036] Comparative Example 1
[0037] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 30 parts of polyphenylene sulfide (PPS 3450), 25 parts of glass fiber, 44 parts of hollow glass microspheres, 0.5 parts of silane coupling agent, and 0.5 parts of antioxidant S9228 were uniformly added into a 280°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0038] Comparative Example 2
[0039] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 84 parts of polyphenylene sulfide (PPS 3450), 10 parts of glass fiber, 5 parts of hollow glass microspheres, 0.9 parts of silane coupling agent, and 0.1 parts of antioxidant S9228 were uniformly added into a 320°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0040] Comparative Example 3
[0041] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 40 parts of polyphenylene sulfide (PPS 3450), 50 parts of glass fiber, 9 parts of hollow glass microspheres, 0.1 parts of silane coupling agent, and 0.9 parts of antioxidant S9228 were uniformly added into a 300°C, 450r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0042] Comparative Example 4
[0043] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 30 parts of polyphenylene sulfide (PPS GAC05), 29 parts of glass fiber, 40 parts of hollow glass microspheres, 0.5 parts of silane coupling agent, and 0.5 parts of antioxidant S9228 were uniformly added into a 280°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0044] Comparative Example 5
[0045] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 30 parts of polyphenylene sulfide (PPS GAT05), 29 parts of glass fiber, 40 parts of hollow glass microspheres, 0.5 parts of silane coupling agent, and 0.5 parts of antioxidant S9228 were uniformly added into a 280°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0046] Comparative Example 6
[0047] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 30 parts of polyphenylene sulfide (PPS GAC20), 29 parts of glass fiber, 40 parts of hollow glass microspheres, 0.5 parts of silane coupling agent, and 0.5 parts of antioxidant S9228 were uniformly added into a 280°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0048] Comparative Example 7
[0049] Preparation of high-performance, high-heat-resistant, low-dielectric constant material: 30 parts of polyphenylene sulfide (PPS 3418), 29 parts of glass fiber, 40 parts of hollow glass microspheres, 0.5 parts of silane coupling agent, and 0.5 parts of antioxidant S9228 were uniformly added into a 280°C, 150r / min twin-screw extruder, and a high-performance, high-heat-resistant, low-dielectric constant material was prepared through base, cooling, and pelletizing.
[0050] Performance Test:
[0051] Tensile strength (MPa): According to GB / T 1040-2018, the tensile strength of the materials prepared in the examples and comparative examples was tested using a universal mechanical testing machine;
[0052] Melt index (g / 10min): According to GB / T 3682-2018, the melt index of the materials prepared in the examples and comparative examples was tested using a melt index measuring instrument;
[0053] Dielectric constant (F / m): According to GB / T 1409-2006, the dielectric constant of the materials prepared in the examples and comparative examples was tested;
[0054] The results are shown in Table 1:
[0055] Table 1
[0056]
[0057]
[0058] Examples 1 to 3 are used to verify the effects of different ratios of raw materials on the material system; Examples 4 to 7 are different from Example 1 in that the types of polyphenylene sulfide are different; Comparative Examples 1 to 3 are different from Examples 1 to 3 in that no metal salt is added; Comparative Examples 4 to 7 are different from Examples 4 to 7 in that the types of polyphenylene sulfide are replaced without adding metal salt;
[0059] Through the above-mentioned embodiments, comparative examples and result comparisons, the use of hollow glass microspheres and low-dielectric glass fibers can significantly reduce the dielectric constant of the PPS material, but the reduction is not large. On this basis, after further adding a small amount of metal salt, the dielectric constant of the composite material is further reduced, and the mechanical properties of the filled PPS material are further improved.
[0060] In summary, the low dielectric constant material with high heat resistance and high performance prepared by the present invention has good mechanical strength, high heat resistance and low dielectric constant, and the hollow glass microspheres, low dielectric glass fibers and metal salts used in the present invention are widely available, low in cost and suitable for large-scale production.
[0061] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A low dielectric constant material with high heat resistance and high performance, characterized in that: Calculated by weight, it includes 30-84 parts of polyphenylene sulfide, 5-50 parts of low-dielectric glass fiber, 5-40 parts of glass microbeads, 0.5-5 parts of metal salt, 0.1-1 parts of antioxidant and 0.1-1 parts of silane coupling agent.
2. The low dielectric constant material with high heat resistance and high performance according to claim 1, characterized in that: The polyphenylene sulfide is one or a combination of PPS 3450, PPS GAC20, GAC09, GAC05, GAC03, PPS 3490, PPS 3418 and PPS GAT05.
3. The low dielectric constant material with high heat resistance and high performance according to claim 1, characterized in that: The glass microspheres are hollow glass microspheres.
4. The low dielectric constant material with high heat resistance and high performance according to claim 1, characterized in that: The metal salts include, but are not limited to, copper bromide, copper chloride, and aluminum oxide.
5. The low dielectric constant material with high heat resistance and high performance according to claim 1, characterized in that: The antioxidant is antioxidant S9228.
6. The low dielectric constant material with high heat resistance and high performance according to claim 1, characterized in that: The silane coupling agent is one or a combination of epoxy silane coupling agent, amino silane coupling agent and urea silane coupling agent.
7. A method for preparing a low dielectric constant material with high heat resistance and high performance as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: Polyphenylene sulfide, low dielectric glass fiber, glass microbeads, metal salt, antioxidant and silane coupling agent are uniformly mixed to obtain a mixture; the mixture is extruded to prepare a low dielectric constant material with high heat resistance and high performance.
8. The method for preparing a low dielectric constant material with high heat resistance and high performance according to claim 7, characterized in that: During the extrusion molding process, the temperature of the twin-screw extruder is 280-320° C. and the rotation speed is 120-450 r / min.
Citation Information
Patent Citations
Poly(phenylene ether) resin composition, prepreg, metal-clad laminate, and printed-wiring board
CN105694425A
High-strength low-dielectric-constant polyphenylene sulfide composition as well as preparation method and application thereof
CN115181423A
Cited By
PPS material and preparation method thereof
CN121779923A
A pps material and a method for preparing the same
CN121779923B